2018
DOI: 10.1093/pm/pny041
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Sympathetic Plexus Block as a Treatment for Postamputation Pain: Methodology for a Randomized Controlled Trial

Abstract: An appropriately powered randomized controlled study using this methodology may not only aid in determining the possible clinical efficacy of lumbar sympathetic block in PAP, but could also improve our understanding of underlying pathophysiologic mechanisms of PAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Acupuncture also stimulates blood flow to restore nerve damage. Acupuncture was found to be an effective treatment option for diabetic and human immunodeficiency virusrelated peripheral neuropathy, especially in Bell's palsy and carpal tunnel syndrome [98][99][100]. Battlefield acupuncture (BFA) is an emerging method of easing neuropathic pain, purported to influence central nervous system pain processing through the release of β-endorphins and its effect on a somatotopic organization of the body represented in the auricle.…”
Section: Complementary and Integrative Medicine (Cim)mentioning
confidence: 99%
“…Acupuncture also stimulates blood flow to restore nerve damage. Acupuncture was found to be an effective treatment option for diabetic and human immunodeficiency virusrelated peripheral neuropathy, especially in Bell's palsy and carpal tunnel syndrome [98][99][100]. Battlefield acupuncture (BFA) is an emerging method of easing neuropathic pain, purported to influence central nervous system pain processing through the release of β-endorphins and its effect on a somatotopic organization of the body represented in the auricle.…”
Section: Complementary and Integrative Medicine (Cim)mentioning
confidence: 99%
“…LSGB provides good analgesia after surgery 63 . With regard to perioperative pain management, LSGB can reduce residual limb pain and PLP during the perioperative period and help patients to recover psychologically after surgery 43 . The causes of pain after lumbar spine surgery are complex.…”
Section: Application Prospect Of Lsgb During the Perioperative Periodmentioning
confidence: 99%
“…Case reports find LSGB is safe and effective for reducing PLP. [43][44][45] Taken together, LSGB has a significant effect on NP relief (Table 1). 46,47…”
Section: Neuropathic Painmentioning
confidence: 99%
“…It is not yet clear what the role may be in PHN [94]. In some cases, it has been hypothesized to be involved in DNP [95] and in PANP treatment [96].…”
Section: Surgical Therapiesmentioning
confidence: 99%
“…It has been demonstrated that acupuncture can be an effective therapeutic option in reducing the pain of diabetic neuropathy and chronic low back pain; however, it is still unclear how effective it is, even though safe and generally well tolerated, in other neuropathic pain syndromes such as post-stroke and post-herpetic neuralgia [96]. Acupuncture has been shown to be safe in many studies, although its efficacy compared to drug therapy has not yet been unequivocally demonstrated [106] and in some cases has proven ineffective.…”
Section: Acupuncturementioning
confidence: 99%